2019
DOI: 10.1136/bmjdrc-2019-000829
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of T cell CD40L has minor beneficial effects on obesity-induced metabolic dysfunction

Abstract: ObjectiveObesity-associated metabolic dysfunction increases the risk of multiple diseases such as type 2 diabetes and cardiovascular disease. The importance of the co-stimulatory CD40-CD40L dyad in diet-induced obesity (DIO), with opposing phenotypes arising when either the receptor (aggravating) or the ligand (protective) is deleted, has been described previously. The functions of CD40 and CD40L are cell type dependent. As co-stimulation via T cell-mediated CD40L is essential for driving inflammation, we here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…For the atherosclerosis studies, Cd40l fl/fl mice were successfully generated via insertion of loxP sites flanking exon 3, which enabled cre-mediated deletion of exon 3 causing a translational frameshift rendering downstream exons nonfunctional (Ozgene Pty Ltd, Bentley, Australia, Supplementary Fig. 1a ) 57 . Cd40 fl/fl mice were successfully generated via insertion of loxP sites flanking exons 2 and 3, which enabled cre-mediated deletion of exon 2 and 3 (Ozgene Pty Ltd, Bentley, Australia, Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For the atherosclerosis studies, Cd40l fl/fl mice were successfully generated via insertion of loxP sites flanking exon 3, which enabled cre-mediated deletion of exon 3 causing a translational frameshift rendering downstream exons nonfunctional (Ozgene Pty Ltd, Bentley, Australia, Supplementary Fig. 1a ) 57 . Cd40 fl/fl mice were successfully generated via insertion of loxP sites flanking exons 2 and 3, which enabled cre-mediated deletion of exon 2 and 3 (Ozgene Pty Ltd, Bentley, Australia, Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…33 We and others have shown that deletion of CD40 or CD40L on different-cell types differentially impact chronic inflammatory disease progression. 4,[11][12][13][14][15][16][17][18] Genetic studies in both patients and mice have shown that CD40L-CD40 signaling might affect BM haematopoiesis and, thus, inflammatory disease progression. 34 It was found that CD40L interaction with CD40 on HSCs induces CD40-TNF receptor associated factor (TRAF)6 signaling, which activated NFκB in HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…13 Furthermore, T-cell specific CD40L-deficiency decreased atherosclerosis by affecting Th1 polarization and IFNγ production 10 , but did not affect weight gain or insulin resistance (IR) in mice with diet-induced obesity (DIO). 14 The CD40 -/mice showed reduced atherosclerosis 15 , as do macrophage 17 , and dendritic cell 10 specific CD40-deficient mice. However, full body CD40deficient mice displayed aggravated IR and severe AT inflammation during DIO 16,19 , whereas deficiency of macrophage CD40 only causes minor obesity related metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 48 ] Therefore, the use of immune checkpoint inhibitors in T2D as a treatment strategy may have a double-edged sword effect whereby it improves T-cell mediated immune responses but further impairing glucose control, as reported elsewhere. [ 49 ] This emphasizes the need to find a fine balance between improving T-cell function while enhancing glucose metabolism when targeting PD-1 signaling as a therapeutic strategy in T2D patients. The overall impact of PD-1 signaling on T-cell function is illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%